Parental beliefs about returns to educational investments—the later the better? - Boneva, T; Rauh, C (Oxford University Press, 2018)
In this paper, we study parental beliefs about the returns to parental investments made during different periods of childhood. Using two independent samples, we document that parents perceive the returns to different late investments to be higher than the returns to early investments, and that they perceive investments in different time periods as substitutes rather than complements. We show that parental beliefs about the returns to investments vary substantially across the population and that individual beliefs are predictive of actual investment decisions. Moreover, we document that parental beliefs about the productivity of investments differ significantly across socioeconomic groups. Perceived returns to early parental investments are positively associated with household income, thereby potentially contributing to the intergenerational persistence in earnings.